Challenging views on population growth. Medium term change in two fast growing African populations in Madagascar and Kenya - (:unkn) unknown (My University, 2019)
Population growth is often pictured as negatively affecting the environment, the economy and individual well-being in Africa. However, in spite of international concerns, fertility remains high in some parts of the continent, and political discourses encouraging large families are still on the agenda in places. Multidisciplinary field research programmes have shown the complexity of the interlinkages between population dynamics, agricultural production and social change. Through two in-depth studies, we wish to illustrate the social and economic changes that enable people to remain in rural areas undergoing high population growth. In Kisii, Kenya, and Vakinankaratra, Madagascar, economic diversification and spatial mobility systems are of growing importance. Intergenerational and gender relationships are changing as well, as can be seen in marriage and inheritance rules. Except in the event of abrupt economic or political change, societies have a capacity to transform, to innovate and overstep social norms in order to make the best of changing settings. Although at macro level, population growth needs to be considered and anticipated, at micro level it might not have such a negative impact. We wish to trigger a discussion on the necessity and the implications of this type of growth, one among others, in the context of developing Africa.
Keywords: African Research